The art of problem solving in organic chemistry - Alonso-Amelot, Miguel E. (Wiley, 2014)
This long-awaited new edition helps students understand and solve the complex problems that organic chemists regularly face, using a step-by-step method and approachable text. With solved and worked-through problems, the author orients discussion of each through the application of various problem-solving techniques. Teaches organic chemists structured and logical techniques to solve reaction problems and uses a unique, systematic approach. Stresses the logic and strategy of mechanistic problem solving -- a key piece of success for organic chemistry, beyond just specific reactions and factsHas.
Keywords: Chemistry, Organic.; Problem solving.; elektronické knihy; electronic books